Bone Mineral Density and Bone Turnover 10 Years After a Single 5 mg Dose or Two 5‐Yearly Lower Doses of Zoledronate in Osteopenic Older Women: An Open‐Label Extension of a Randomized Controlled Trial. (13th October 2021) - Grey, Andrew; Bolland, Mark J; Horne, Anne; Mihov, Borislav; Gamble, Greg; Reid, Ian R
ABSTRACT: Intravenous zoledronate reduces fracture risk (5 mg at 18‐month intervals) and prevents bone loss (doses of 1 to 5 mg for 3 to >5 years), but the duration of action of a single 5 mg dose and the effects of lower doses beyond 5 years are unknown. We report the second open‐label extension (years 5 to 10) of a 2‐year randomized, multidose, placebo‐controlled, double‐blinded trial. A total of 116 older women who completed 5 years of participation either continued observation without further treatment (zoledronate 5 mg and placebo at baseline) or received repeat doses of 1 or 2.5 mg zoledronate (zoledronate 1 mg and zoledronate 2.5 mg at baseline, respectively). Outcomes were spine, hip, and total body bone mineral density (BMD) and serum markers of bone turnover. After a single 5 mg dose of zoledronate, mean BMD at the lumbar spine and total hip was maintained at or above baseline levels for 9 and 10 years, respectively. The mean level of the bone resorption marker β‐C‐terminal telopeptide of type I collagen (β‐CTX) was at least 25% lower than that in the placebo group for 9 years. In women administered 5‐yearly doses of 2.5 mg zoledronate, mean BMD at the total hip and lumbar spine was maintained at or above baseline levels for 9 and 10 years, respectively. Redosing with 1 or 2.5 mg zoledronate at 5 years reduced bone turnover markers for 3 to 4 years. BMD increased for 3 to 4 years after redosing with 1 mg zoledronate. In the group given 5‐yearly 2.5 mg zoledronate, β‐CTX was at least 20% lower than that in the placebo group for 10 years. Both a single baseline 5 mg dose of zoledronate and 5‐yearly doses of 1 and 2.5 mg zoledronate prevented bone loss at hip and spine for 8 to 10 years in older postmenopausal women. Clinical trials to evaluate the effects on fracture risk of these very infrequent and lower doses of zoledronate are justified. © 2021 American Society for Bone and Mineral Research (ASBMR).